Fuzzy Logic as A Private College Marketing Strategy in Efforts to Increase The Amount of Receipt of New Students - Fidziah Fidziah; Suhroji Adha (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
The choice of marketing strategy for the Banten College of Economics (STIEB) is something that is very urgent because STIE Banten is one of the representations of higher education institutions in the field of economics which cites the name Banten as a primordial characteristic. Choosing the right marketing strategy is something that is expected and becomes an alternative for a decision that will be chosen later. The alternatives to be achieved are alternatives that contain several criteria that must be assessed based on priority. The selection of alternative strategies resulted from a SWOT analysis. The strategy development of the Banten College of Economics is faced with an ambiguous or uncertain decision so that decision makers have difficulty in determining their decisions. Usually decision makers use intuition and subjectivity only the objectives and stages of the research method. This study generally aims to develop a SWOT analysis and fuzzy logic as a marketing strategy as a solution to increasing the number of new student admissions. This research uses two analysis methods, namely: SWOT analysis In conducting a SWOT analysis, the stages of the research method carried out are as follows: Swot Method , Internal Strategy Factor Matrix, External Strategy Factor Matrix, Assessment, Swot Matrix, Fuzzy Alnalytic Hierarchy Process (F-AHP), Comparative Calculations between alternatives. The results of the analysis using FUZZY LOGIC and SWOT on the marketing strategy of the Banten College of Economics obtained a concept ideas about exploring all the potential to minimize weaknesses and use strengths to take advantage of opportunities and face threats. Based on the analysis of F-AHP in determining priority development sectors and making recommendations for marketing strategies of the Banten College of Economics.